Structural analysis of palm oil mill fly ash (POFA) as a low cost alternative in water treatment: article - Norsham, Nur FatinHanani Fatimah; Othman, Nur Hidayati (2019)
Palm oil mill fly ash (POFA) is known to exhibit pozzolanic property. The abundance and easily available of POFA in Malaysia make it an attractive alternative to be fabricated as a ceramic membrane in water treatment. As POFA membrane has high permeability and low selectivity, it is usually coated with graphene. Graphene oxide (GO) and reduction of graphene oxide (rGO) using an environmentally friendly agent was synthesized and the characteristic was studied alongside with POFA membrane. In depth study is done to determine the most suitable composition and casting method to successfully fabricate POFA membrane. The characteristics of the synthesized membranes were performed by using X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF) Spectroscopy, Thermal Gravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR) and Hg Porosimetry Micromeritics. The result revealed that POFA contained high amount of silica which made it pozzolanic with 67.65% porosity. The high porosity of POFA membrane render it as a good choice in wastewater treatment.